Laser Doppler fluxmetry - Sarnik, Stanislav; Hofirek, Ivo; Sochor, Ondrej (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2007)
BACKGROUND: Laser Doppler fluxmetry (LDF) is an extraordinary sensitive noninvasive method of examination. It can be used for monitoring changes in the cutaneous peripheral microcirculation(15). It uses a monochromatic low-energy laser beam. This beam penetrates the tissue and, depending on individual tissue penetration, it is reflected, recorded by a sensitive sensor and subsequently analyzed using the Doppler. Laser Doppler fluxmetry detects movement of cells in the peripheral circulation and microcirculation. METHODS: The light from the laser source is delivered via optical fibers to the tissue. In the tissue the light collides with moving blood elements; after a collision, the wave length of the light changes--this phenomenon is called Doppler shift. Our own method of measurement has already been fully developed. We have a group of patients with physiological findings and also groups of patients with vasoneurosis, patients with type 1 diabetes mellitus, vasculitis patients, and other patient groups. We examine the blood flow on the dorsal side of fingers or toes. There are many protocols for laser Doppler examination. For all the patient groups we used a protocol evaluating an algorithm, developed in the training department of the Perimed company, using provocation tests for the assessment of the vascular wall function in addition to records at rest. USE OF LASER DOPPLER: We have developed a method of use of laser Doppler examination in about 8 years. We have examined several groups of patients. First a patient group with physiological findings was examined, and subsequently groups of patients with vasculitis, vasoneurosis, and a group of patients with type l diabetes mellitus. Recently, monitoring has been performed in patients after cardioversion in chronic atrial fibrillation with sinus rhythm restitution, and also data obtained before and after a varicose vein operation on lower limbs have been compared. CONCLUSION: Clear diagnostic criteria for this method do not exist so far. For the time being this is a rather theoretical method that we used even in practice for the above mentioned diseases. The method provides enough data even for more detailed analyses. The information value of the curve arises after statistical data analysis with the t-test.
Keywords: regionální krevní průtok; Vascular Diseases; Regional Blood Flow; Humans; lidé; Laser-Doppler Flowmetry; nemoci cév; laser doppler flowmetrie